2022
DOI: 10.1371/journal.pone.0273860
|View full text |Cite
|
Sign up to set email alerts
|

AI-based search for convergently expanding, advantageous mutations in SARS-CoV-2 by focusing on oligonucleotide frequencies

Abstract: Among mutations that occur in SARS-CoV-2, efficient identification of mutations advantageous for viral replication and transmission is important to characterize and defeat this rampant virus. Mutations rapidly expanding frequency in a viral population are candidates for advantageous mutations, but neutral mutations hitchhiking with advantageous mutations are also likely to be included. To distinguish these, we focus on mutations that appear to occur independently in different lineages and expand in frequency i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Independently of the present study, our group have shown that variant-specific clustering, and thus variant-specific feature extraction, is possible by using an unsupervised AI suitable for analysis of a large number of variables and thus of long oligonucleotides [ 22 , 23 , 35 ]. By analyzing the usage of long oligonucleotides (e.g.,20-mers) in Omicron and other variants, we have recently characterized advantageous mutations that spread convergently in multiple lineages [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Independently of the present study, our group have shown that variant-specific clustering, and thus variant-specific feature extraction, is possible by using an unsupervised AI suitable for analysis of a large number of variables and thus of long oligonucleotides [ 22 , 23 , 35 ]. By analyzing the usage of long oligonucleotides (e.g.,20-mers) in Omicron and other variants, we have recently characterized advantageous mutations that spread convergently in multiple lineages [ 36 ].…”
Section: Resultsmentioning
confidence: 99%